A gestão da comunicação pública de estado em municípios de pequeno porte: um estudo empírico a partir dos princípios da governança com vistas à proposição de boas práticas - Maduro, Maiara Carvalho Batista (2024)
As a rule, communication within public bodies should be a tool for accountability and transparency. However, these principles are often contradicted in practice, especially in bodies whose management is renewed in electoral cycles, . In this sense, this thesis aims to qualitatively analyze public communication practices in small municipalities based on specific theoretical and legal frameworks in the fields of communication and public governance. Based on empirical research conducted in Santa Catarina — a state where 75% of municipalities are small — the work analyzes aspects such as professional development, workflow, production of news content, use of digital platforms, the profile of the public communicator, political interference and the role of public communication in city halls of municipalities with less than 20 thousand inhabitants. Methodologically, the research used four data collection methods: an online questionnaire answered by 98 city halls, on-site observation and in-depth interviews in two municipalities, and the recording of digital information content from three city halls. The results highlight a heterogeneous scenario, with variations in the profile and valuation of professionals in the area, as well as similarities in workflow and the use of digital platforms and tools for producing news content. The research concludes that political interference and the growing responsibility of public communication are relevant challenges, especially in municipalities where the local press is weakened. In addition, the thesis points to the need to recognize communication as an essential public service, requiring regulation, professionalization, and valorization to strengthening citizenship and democracy at the local level. This investigative process resulted in a set of technical guidance products — including an e-book, a podcast, and a kit of editable materials -, developed to support public communication employees in city halls of small municipalities, helping them to overcome challenges and adopt more effective public communication practices.